BIMBINGAN BAGI ANAK BERPERILAKU MASALAH DI SD GMIT 022 MOLA - Enjel Maryana Weni; Halena Makunbok, Elsa Miranda Lanmai, Yessy Mata, Petrus Mau Tellu Dony, Yeremia S. Wabang (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
The purpose of this study is to identify the problems faced by students at UPTD SD Gimt 002 Mola, the actions taken by guidance and counseling teachers to assist the students. This is a descriptive qualitative study by type, and the results show that internal and external factors are the causes of students' problems in elementary school. Internal factors are those related to the individual, while external factors include (1) students' tendency to be lazy, (2) emotional tendencies, and (3) intentional actions. External factors include family, school, and social environment. In dealing with students who experience problems, the guidance and counseling teacher uses (1) individual counseling, (2) group counseling, (3) group guidance, and (4) social rehabilitation. In the counseling process, the guidance teacher interviews students in groups. Based on the explanation, students who do not engage in problematic behavior will not receive sanctions, while students who do will receive appropriate sanctions based on the explanations given. After the sanctions are administered, whether in the form of school attendance, class rules, counseling, or parents, the students are then given group guidance sessions to help them resolve their issues. Social rehabilitation observes how students who have received counseling function socially in line with social changes and their status.